Molecular detection of Cooperia oncophora and Ostertagia ostertagi in cattle: Comparison of sample processing and detection on ddPCR and qPCR platforms - Woolsey, Ian David; Opsal, Tonje; Robertson, Lucy; Ptochos, Sokratis; Hektoen, Lisbeth (Experimental parasitology, 2025)
Faecal samples were obtained from 77 first season grazers from 20 Norwegian dairy herds in autumn 2020 for analysis of Cooperia oncophora and Ostertagia ostertagi infection. Strongylid eggs per gram of faeces (EPG) were determined for each sample and the samples underwent larval culture. DNA was extracted from the faeces at different stages of the culture preparation: from faecal slurry (FS), direct extraction before culture (DBC), and direct extraction after culture (DAC). Extracted DNA was subject to molecular assay for both C. oncophora and O. ostertagi using both a published ddPCR assay and a modified qPCR duplex assay targeting the ITS-2 gene. For C. oncophora, DBC samples contained significantly less ITS-2 copies than DAC and FS samples (p ≤ 0.0001 for both) for qPCR, but not between DAC and FS samples (p = 0.339). Droplet digital PCR with DBC samples yielded significantly fewer ITS-2 copies than DAC and FS samples (p ≤ 0.0001). For O. ostertagi, the ITS-2 copies in DBC samples differed significantly from levels in DAC and FS samples on the qPCR platform (p=0.002 and 0.044, respectively) as was the case with ddPCR (p ≤ 0.0001 and 0.0137). Overall, across the various processing techniques, C. oncophora results obtained on both ddPCR and qPCR platforms correlated with EPG better than was found for equivalent results for O. ostertagi and results are strongly indicative of poor correlation when EPG counts are low. Results from this study suggest that DAC faecal processing was of limited practical use. [Display omitted] •DNA extraction after faecal processing techniques were compared with ddPCR and qPCR.•These results were correlated with EPG data on the same samples.•There was broad agreement between the two molecular platforms.•Larval culture conveys little benefit to sensitivity.•Correlation with EPG were significantly lower with low level infections.